Microalbuminuria and sRAGE in High-Risk Hypertensive Patients Treated with Nifedipine/Telmisartan Combination Treatment: A Substudy of TALENT. (13th February 2012) - Falcone, Colomba; Buzzi, Maria Paola; Bozzini, Sara; Boiocchi, Chiara; D'Angelo, Angela; Schirinzi, Sandra; Esposito, Ciro; Torreggiani, Massimo; Choi, Jasmine; Ochan Kilama, Michael; Mancia, Giuseppe
Abstract : Some antihypertensive drugs have also renoprotective and anti-inflammatory properties that go beyond their effect on blood pressure. It has been suggested that microalbuminuria and glomerular filtration rate (GFR) are associated with circulating levels of the soluble form of the receptor, sRAGE (soluble receptor for advanced glycation ends-products). In the present analysis, we used data from the TALENT study to evaluate soluble receptor for advanced glycation end-products (sRAGE) plasma levels in patients with hypertension and high-cardiovascular risk-treated nifedipine and telmisartan in combination. Treatment with nifedipine-telmisartan significantly decreased mean systolic and diastolic ambulatory blood pressure and resulted in a significant increase in sRAGE plasma concentrations after 24 weeks of therapy. We concluded that in hypertensive patients with early-stage renal disease, sRAGE concentrations are not influenced by either microalbuminuria or GFR. Long-term treatment with a combination of nifedipine-telmisartan may have a beneficial effect increasing sRAGE plasma levels, thus exerting an atheroprotective and anti-inflammatory activity.